PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN QUESTION CARD TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN PPKN MATERI HAK DAN KEWAJIBAN DI KELAS IV SD - Rihhadatul Aisy, Shaafiyah; Mahya Fanny, Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education plays a crucial role in developing high-quality human resources, particularly in facing 21st-century challenges that require critical thinking skills. However, the learning process in elementary schools is still dominated by teacher-centered approaches, resulting in low students’ critical thinking abilities, especially in Civics Education (PPKn). This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by Question Cards on students’ critical thinking skills in learning rights and obligations in grade IV elementary school. This research employed a quantitative approach with a quasi-experimental design using a pretest-posttest non-equivalent control group design. The study was conducted at SDN Margorejo I/403 Surabaya with a total sample of 50 students divided into experimental and control groups. Data were collected through essay tests and analyzed using normality, homogeneity, and independent samples t-test with SPSS 25. The results showed that the average score of the experimental class increased from 52.2 (pretest) to 84.2 (posttest), while the control class increased from 38.4 to 67.8. The hypothesis test indicated a significance value of 0.000 < 0.05, meaning that there is a significant effect of the PBL model assisted by Question Cards on students’ critical thinking skills. Therefore, this model is effective in improving students’ active participation and critical thinking in PPKn learning.